PENGELOLAAN SAMPAH SKALA RUMAH TANGGA SECARA MANDIRI BERBASIS “ZERO WASTE” - NI MADE NIA BUNGA SURYA DEWI (GANEC SWARA, 2018)
"Zero waste" management is the management by sorting, composting and collecting of goods worth selling.The segregation of household waste should be supported by adequate waste bin facilities. Trash bin that must be provided in the house must be divided into 2 types of waste, namely organic waste (wet) and inorganic waste (dry). Waste that has been separated into wet and dry then carried out the management of composting and collecting of waste worth selling. Composting is a technique to process organic waste in the form of waste of food, vegetables and fruit scraps or kitchen waste. If organic household waste is managed independently (on site) by composting them then inorganic waste must be managed with the help of a third party (off site). Third parties that can support domestic inorganic waste management are informal recycling entrepreneurs, among others, garbage pickers, craftsmen of special recycling products for aluminum foil coated plastic packaging as well as a rising new alternative that is saving garbage in garbage bank.